Implementing an electrical fractional potential through a genetic algorithm - Jesus, Isabel S. (2019)
Several phenomena present in electrical systems, motivated the development of comprehensive models based on the theory of fractional calculus (FC). Bearing these ideas in mind, in this work, are applied the FC concepts to define, and to evaluate, the electrical potential of fractional order based in a genetic algorithm optimization scheme. Research on the approximation feasibility and convergence is also developed.